Cardiovascular Risk Factors Among People Being Treated for HIV in Nepal: A Cross-Sectional Study - Nirmal Aryal; Debbi Marais; Padam Simkhada (Journal of Clinical Research In HIV AIDS And Prevention, 2014)
Background: Human Immunodeficiency Virus (HIV) and antiretroviral therapy (ART) are found to be strongly associated with cardiovascular diseases. Data are sparse on the prevalence and distribution of cardiovascular risk factors among people being treated for HIV in South Asia region. Methods: A cross-sectional study of 103 HIV patients (51 women and 52 men) attending routine follow-up consultations at the largest ART centre in Nepal was conducted. Data on several cardiovascular risk factors were collected through interview questionnaires, biophysical measurements and consulting medical records. Results: The most common cardiovascular risk factors observed were central obesity 34.6% 95% Confidence Interval (CI): 25.3% to 43.9%, chronic kidney disease 20.7% (95% CI: 11.6% to 29.7%) and tachycardia 20.6% (95% CI: 12.7% to 28.5%). Females were significantly more likely to have central obesity (male 9.8% vs. female 60%, p=0.016) and chronic kidney disease (male 15.4% vs. female 26.3%, p=0.003) as compared to the males. Participants were fairly active but a large proportion, especially men, had smoked 65% (95% CI: 57%-72.3%), used tobacco products 66% (95% CI: 56.4%-74.4%) or drugs (53.8% of the men) and consumed alcohol 60.2% (95% CI: 50.5%-69.1%). Conclusion: A high prevalence of several cardiovascular risk factors was observed among patients being treated for HIV in Nepal. Further larger studies are warranted to better understand the relevance and public health impact of cardiovascular risk factors in this region.
Keywords: HIV